2015
DOI: 10.1039/c5gc00262a
|View full text |Cite
|
Sign up to set email alerts
|

Lipase purification using ionic liquids as adjuvants in aqueous two-phase systems

Abstract: ARTICLE This journal isAqueous two-phase systems (ATPS) are efficient, environmentally friendly, and "biocompatible" separation processes, which allow the recovery of enzymes. The most common systems are based on polymers and salts, and recently, to overcome the low polarity difference between the phases of the polymeric systems, ATPS based on ionic liquids (ILs) were proposed and have been successfully applied on the field. This work discusses the use of imidazolium-based ILs not as phase forming compounds bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 37 publications
0
57
0
Order By: Relevance
“…Traditionally, the most common combination was a polymer and a salt. However, since 2003, when Rogers et al [9] reported the ability of ionic liquids to trigger phase disengagement, many authors have applied this kind of systems for the separation of a variety of biomolecules like enzymes [10,11], antioxidants [12] or alkaloids [13], among others. Several reasons justify the interest in applying ionic liquid-based ABS in the extraction of this type of molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the most common combination was a polymer and a salt. However, since 2003, when Rogers et al [9] reported the ability of ionic liquids to trigger phase disengagement, many authors have applied this kind of systems for the separation of a variety of biomolecules like enzymes [10,11], antioxidants [12] or alkaloids [13], among others. Several reasons justify the interest in applying ionic liquid-based ABS in the extraction of this type of molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the high solubility of most ILs in water at room temperature, usually large concentrations of salts are required to promote the ATPS formation, turning these processes more expensive and less sustainable. The use of small quantities of ILs as adjuvants in polymer-based ATPS appears as an alternative to overcome these difficulties [7,11,1619]. …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the ILs have a minor effect upon the ATPS formation, and that the partition coefficients values obtained in the systems with ILs are lower than in systems without them. The same authors [16] studied the extraction of lipase produced by submerged fermentation by Bacillus sp. ITP-001 using imidazolium-based ILs as adjuvants (5 wt%) in ATPS composed of PEG (1500, 4000, 6000 and 8000) and potassium phosphate buffer at pH 7.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, IL‐ATPSs potentially have a higher selectivity, flexibility and can provide more efficient separations than commonly used ATPSs composed of polymer‐polymer or polymer‐salt . However, reports on integrated separation processes of biomolecules from biomass using ATPSs and IL‐ATPSs are limited . The application of IL‐ATPSs is generally studied using pure biomolecules (e.g.…”
Section: Introductionmentioning
confidence: 99%